An econometric analysis of selected determinants of foreign direct investment - Rahimov, Mohammad Ali (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
ABSTRACT: The main focus of this thesis is to analyze the impact of some variable such as Inflation rate, GDP Growth, Financial Development and openness on Foreign Direct Investment (FDI), in selected emerging economics. The sample of countries includes Turkey, Argentina, India, Poland and Hungary. In this study Pooled Regression Analysis will be used to estimate the general effect of some economic variables such as Financial Development, Inflation Rate, Growth Rate of GDP and Openness on FDI based on the data of all countries in our sample. In addition, we will add several control variables as variables to the right side of our Foreign Direct Investment equation such as last year's FDI or last year Financial Development. At last, this study will present that how each economic variable will effect on Foreign Direct Investment; on the other hand this thesis will present the amount of effect of each economic variable on Foreign Direct Investment. Keywords: Foreign Direct Investment, Financial Development, Inflation Rate, GDP, Openness. ………………………………………………………………………………………………………………………… ÖZ Bu tezin ana hedefi, gelişmekte olan ekonomilerde Doğrudan Yabancı Yatırım (DYY) Enflasyon oranı, GSYİH Büyüme, Finansal Gelişme ve açıklık gibi bazı değişken etkisini analiz etmektir. Ülkelere örnek olarak Türkiye, Arjantin, Hindistan, Polonya ve Macaristan göstere biliriz. Bu çalışmada Toplanmış Regresyon Analizi Finansal Gelişme, Enflasyon Oranı, GSYİH Büyüme Hızı ve bizim örnek tüm ülkelerin verilerine dayanarak DYY üzerindeki açıklık gibi bazı ekonomik değişkenlerin genel etkisini tahmin etmek için kullanılır. Ayrıca, değişken olarak bizim Doğrudan Yabancı Yatırım denklemin sağ tarafında geçen yılki DYY veya geçen yıl Finansal Gelişme gibi birkaç kontrol değişkenleri katacağız. Son olarak, bu çalışma nasıl her ekonomik değişkenin Doğrudan Yabancı Yatırımı etkilediğini sunacak; diğer taraftan bu tez, her ekonomik değişkenin Doğrudan Yabancı Yatırım üzerindeki etkisi miktarını sunacak. Anahtar Kelimeler: Doğrudan Yabancı Yatırım, Finansal Gelişme, Enflasyon Oranı, GSYİH, Açıklık.
Master of Business Administration. Thesis (M.B.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2013. Supervisor: Prof. Dr. Serhan Çiftçioğlu.
Keywords: Business Administration; International Business Enterprises; Investments, Foreign; Foreign Direct Investment, Financial Development, Inflation Rate, GDP, Openness